2nd International Conference on Advances in Medical Science and Molecular Biology 2020: Life Sciences-Biology - Sr.Claudine Arokiamary, CHIEF PATRON (International Journal of Life Science and Pharma Research, 2020)
The articles published in the special issue with developing field of biological sciences which has many important applications. This publication would not be possible without the tremendous contribution of authors and reviewing committee. Their contribution and efforts are greatly appreciated.